Pemberdayaan Kelompok Budidaya Ikan di Kelurahan Sungai Lulut melalui Teknologi Pembuatan Pakan Herbal Daun Kelor dan Edukasi Ikan sebagai Nutraseutikal Pencegah Stunting: The Driving Force of Fish Farming Group in Sungai Lulut Village through the Technology of Herbal Moringa Leaf Feed Production and Education on Fish as a Nutraceutical to Prevent Stunting - Niah, Rakhmadhan; Prihandiwati, Erna; Aisyah, Noor; Dharmaji, Deddy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The issue "Jaya Makmur" is low quality and quantity of fish production, primarily due to reliance on suboptimal instant feed and insufficient fish utilization to combat stunting in Sungai Lulut. This activity aims to enhance fish production quality and quantity, processing herbal feed from moringa leaves, and educating the community to help reduce stunting. The method of this activity includes socialization, training in producing herbal feed and eco-friendly mixing tools, application of technology, assistance, evaluation, utilization of unused land, and continuous monitoring to enhance production and establish distribution partnerships, all while educating about stunting.The success of this program is reflected in the improvement of partner skills in making natural feed, feed management, and the production of fish-based nuggets and meatballs for complementary feeding (MPASI). The challenge currently faced is that many fish farmers still rely on instant feed, so further efforts are needed to encourage the transition to herbal feed.